2002
DOI: 10.2188/jea.12.33
|View full text |Cite
|
Sign up to set email alerts
|

Parental Obesity, Lifestyle Factors and Obesity in Preschool Children: Results of the Toyama Birth Cohort Study.

Abstract: The aim of this study was to clarify the impact of parental obesity and lifestyle factors on obesity in preschool children. The subjects consisted of 8941 children aged 3 years, born in 1989. Anthropometric measurements and questionnaire surveys were conducted between 1992 and 1994. Subjects of body mass index (BMI; (weight (kg))/(height (m))2) more than the age- and sex-specific centiles linked to adult overweight were defined as obese subjects. Parental obesity was defined as BMI of 25 kg/m2 or more. Logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
2
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 19 publications
(32 reference statements)
8
100
2
3
Order By: Relevance
“…This negative association has been reported in previous studies. 43,44 It has been suggested that this relationship may be the result of a hormonal mechanism, such as reduction in growth hormone secretion and increase in serum cortisol concentration. At this stage it is not possible to determine whether overweight causes lack of sleep, whether short sleeping duration results in weight gain or whether the association is to due to other confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…This negative association has been reported in previous studies. 43,44 It has been suggested that this relationship may be the result of a hormonal mechanism, such as reduction in growth hormone secretion and increase in serum cortisol concentration. At this stage it is not possible to determine whether overweight causes lack of sleep, whether short sleeping duration results in weight gain or whether the association is to due to other confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…4 A total of 15 observational studies published between 1994 and 2004 were reviewed, including 2 longitudinal studies, 36,68 2 nationally representative studies, 57,69 and 11 other cross-sectional studies. 42,60,[70][71][72][73][74][75][76][77][78] The ADA concluded that the preponderance of evidence suggested that breakfast skipping may be a risk factor for increased adiposity, particularly among older children or adolescents. However, the strength of the evidence is somewhat limited because what constitutes a breakfast has not been defined consistently.…”
Section: Breakfast Skippingmentioning
confidence: 99%
“…The Lifeways study was one of the first to show that general practitioner-reported wheeze or asthma (52) Czech Republic 7577 1994 x Devereux et al (53) UK 1400 1997 x x Drouillet et al (54) France 1900 2003 x x x x Dubois et al (55) Canada 1450 1998 x x Eggesbo et al (56) Norway 2500 2003 x x x Emanuel et al (57) UK 3076 1958 x Gorden-Larsen et al (58) USA 14 706 1995 x Gracie et al (59) Canada 3388 2008 x x Grandjean et al (60) Faroe Islands 1022 1986 x x x x Guldner et al (61) France 4000 2002 x x Guxens et al (62) Spain 3768 1997 x x x x x Grazuleviciene et al (63) Lithuania 4405 2007 x Hawkes et al (64) Ireland 2185 2008 x Hawkins et al (65) UK 13 113 2000 x Hill et al (66) Wales 420 2009 x x Hryhorczuk et al (67) Ukraine 4510 1992 x x x Hui et al (68) Hong Kong 8327 1997 x x Hunt et al (69) Canada 521 1981 x x Inskip et al (70) UK 3159 1998 x x Jaddoe et al (71) Netherlands 10 000 2002 x Jedrychowski et al (72) Poland 432 2000 x x Kaplowitz et al (73) UK 224 1986 x x Karvonen et al (74) Finland 442 2002 x x x x Katier et al (75) Netherlands 2500 (95) Germany 2000 2011 x x x x Richiardi et al (96) Italy 7500 2005 x x x x Schaefer-Graf et al (97) Germany 324 1995 † x x Sekine et al (98) Japan 8941 1992 x x Skalkidou et al (99) Sweden 580 2009 x x Tsuchiya et al (100) Japan 1260 2007 x x van Eijsden et al (101) The Netherlands 6161 2003 x x x x Vandentorren et al (102) France 20 000 2011 x x x Vecchi Brumatti et al (103) Italy 900 when the child averaged 3 years was inversely associated with maternal fruit and vegetable and fish consumption during pregnancy (1...…”
Section: Dietary Patterns and Risk Of Childhood Wheezing Or Asthmamentioning
confidence: 99%